Promissory Note in Securing Corporate Debts - Lidia WLODARSKA-ZOLA (Communications of International Proceedings, 2021)
The subject of this article is the role of promissory note in securing corporate debts. The aim of the article is to discuss the premises of the promissory note, the formal and legal nature of the promissory note as well as the features and functions that determine the use of the promissory note in trade. The first part of the study presents the historical outline of the creation of the promissory note and the development of the promissory note law. The second part describes the promissory note, its formal and legal elements and specific features that determine not only the nature of the promissory note debtors' liability, but also the procedure for pursuing claims under the promissory note. The considerations presented in the third part focus on the use of the promissory note as an instrument for securing corporate debts. The applied research method is literature studies on the basis of selected scientific studies and legal acts.
Keywords: Promissory Note; Trading In Promissory Notes; Debt Security